2013
DOI: 10.1364/oe.21.031919
|View full text |Cite
|
Sign up to set email alerts
|

Transmission phase gratings fabricated with direct laser writing as color filters in the visible

Abstract: Simple diffraction structures having the form of a regular grid of pillars can generate a significant range of hues in white light transmission due to color-dependent diffraction into higher orders. We present the fabrication of such submicrometer scale structures by three dimensional laser two-photon photolithography, results of their optical properties measurements and compare the latter with numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…These structures give rise to diverse functions ranging from mechanical strengthening (11) and directional adhesion (12,13) to superhydrophobicity (14) and structural colors (15), thus inspiring researchers to devote their efforts to mimic these multifunctional structures for decades. Many top-down fabrication approaches such as photolithography together with deep dry etching (16), replica molding (14, 17), multibeam laser interference lithography (18,19), and electron-beam lithography (20) have been used in combination with capillary force self-assembly to produce hierarchical structures.…”
mentioning
confidence: 99%
“…These structures give rise to diverse functions ranging from mechanical strengthening (11) and directional adhesion (12,13) to superhydrophobicity (14) and structural colors (15), thus inspiring researchers to devote their efforts to mimic these multifunctional structures for decades. Many top-down fabrication approaches such as photolithography together with deep dry etching (16), replica molding (14, 17), multibeam laser interference lithography (18,19), and electron-beam lithography (20) have been used in combination with capillary force self-assembly to produce hierarchical structures.…”
mentioning
confidence: 99%
“…Electro-optical polymer based devices are another area of study which has been taking advantage of the MPM as a powerful characterization method [9]. Moreover, recent studies showed the ability of utilizing MPM in three dimensional micro-fabricated devices including sensors, waveguides, photonic structures, and biomedical devices, using various types of light sensitive polymers [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Provided its chemical material properties; its inert, non-toxic and surface is hydrophobic [1]. With other multipurpose properties such as viscoelastic with excellent optical and rheologic attributes [2], they are used as a structural material in microfluidic systems and biosensors often [3,4], narrowline feedback elements [5], tunable optical filters [6], polarization beam splitters [7], dispersion engineering [8], microwave frequency selective elements [9,10], and color filters [11][12][13]. By nature, the surface of PDMS is hydrophobic which presents a challenge in micro-channels.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous treatments such as O 2 , C 2 F 2 , SF 6 , CF 4 , SiCl 4 , CCl 4 or mixture of the gases have been practical on PDMS surface to improve its hydrophobic properties. Besides, PDMS as a substrate or a structural material also growing according to the variety of design choices by post processing methods such as etching, coating, polishing, deposition and surface modification [1][2][3][4][5][6][7][8][9][10][11][12]. These efforts have merely been made specifically for PDMS enhancement and treatment, yet not any attempt is available on purely PDMS based properties as a substrate.…”
Section: Introductionmentioning
confidence: 99%